1990
DOI: 10.1080/00039896.1990.10118751
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Fatal Lung Disease in Three Utah Counties

Abstract: A unique situation found in two Utah counties has made it possible to estimate the fraction of respiratory cancer and nonmalignant respiratory disease (NMRD) deaths, which are attributable to community air pollution (CAP) in one county. The two counties were very similar in many ways, including low smoking rates, until a steel mill constructed during WW II caused substantial CAP in one of them. Subsequent differences in mortality rates from both respiratory cancer and NMRD are striking. A third county, similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 36 publications
1
36
1
Order By: Relevance
“…After adjusting for differences in socioeconomic characteristics, the relative risk of respiratory post-neonatal respiratory mortality was approximately 3.00 for most polluted areas versus least polluted areas. Archer, 1990 (91) Three counties in Utah Spatial and longitudinal differences in death rates in three counties with low smoking rates and the introduction of a major pollution source were evaluated. It between young, nonsmoking children; and 3) cigarette smoking does not change dayto-day, week-to-week, or month-to-month in positive correlation with air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for differences in socioeconomic characteristics, the relative risk of respiratory post-neonatal respiratory mortality was approximately 3.00 for most polluted areas versus least polluted areas. Archer, 1990 (91) Three counties in Utah Spatial and longitudinal differences in death rates in three counties with low smoking rates and the introduction of a major pollution source were evaluated. It between young, nonsmoking children; and 3) cigarette smoking does not change dayto-day, week-to-week, or month-to-month in positive correlation with air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Within``polluted'' areas, exposure subgroups were formed using proximity measures in six studies. Air pollution levels were quantified using monitoring data in three studies ( Brown et al, 1984;Andre Ân et al, 1988;Archer, 1990) and by dispersion modeling in a fourth (Dales et al, 1989 ).…”
Section: Study Characterizationmentioning
confidence: 99%
“…There are many possible reasons for insignificance (Roht et al, 1985;Schulman et al, 1993;Acquavella et al, 1994;Nurminen, 1995 ). As examples, the studies suggested the possibility of sampling and measurement bias ( Willis et al, 1993;Garcõ Âa -Rodrõ Âguez et al, 1996;Morris and Knorr, 1996 ), confounding ( Heary et al, 1980;Archer, 1990;Baghurst et al, 1992;Kilburn and Warshaw, 1995;Pope et al, 1995 ) , insufficient sample size and statistical power (Greaves et al, 1981;Matanoski et al, 1981;Brown et al, 1984;Rosenman et al, 1989;Aschengrau et al, 1996 ) , lack of baseline data ( Willis et al, 1993 ) , and residence mobility Pekkanen et al, 1995 ) . In addition, invalid or inaccurate exposure estimates are likely to weaken associations between exposures and effects, whereas inadvertent association between erroneous exposure estimates and other cofactors might yield false associations.…”
Section: Validity Of Residence Location As An Exposure Indicatormentioning
confidence: 99%
See 1 more Smart Citation
“…Stevens and Moolgavkar (36) deduced that there had been declines in lung cancer incidence among nonsmoking males in England and Wales coincident with substantial declines in levels of particulate and sulfur dioxide pollution that resulted from the implementation of nationwide air pollution control measures. * In another study, Archer (34) analyzed respiratory cancer mortality in two Utah counties with very low smoking rates. These two counties were similar in many respects, with low and nearly equal respiratory cancer mortality rates until a steel mill constructed during World War II caused substantial increases in air pollution in one of them.…”
Section: Environmental Exposurementioning
confidence: 99%